Hermeneutics and pedagogy. Educational practicein the speech abaut education - García Bravo, William; Martín Sánchez, Miguel A. (Pulso. Revista de educación, 2013)
In this paper we reflect on the relationship be¬tween educational practice and the theoretical discourse on the practice. From a hermeneutic approach, we analyzed the relationship, within the pedagogical field, between the issues of certitude, validation and evidence to qualitative inquiry. In this regard, the proposal of a «hermeneutical circle of interpretations» built up by numerous in¬terpreters when a text or a fact-resembled text is under scrutiny does not resolve the above men¬tioned task. We propose a reasonable level of validation in order to break down the circle of free interpretations, being achieved through analysis and reflection of three channels: the strength of interpretative argument, the scholar community consensus and the educational practice itself. It concludes with the idea that educational practice itself is the best way to validate the theory.